Homossexualidade, religião e gênero: a influência do catolicismo na construção da auto-imagem de gays e lésbicas - Busin, Valéria Melki (2008)
The homosexuality, as well as the inequality between genders, was biologized and naturalized at the end of the eighteenth century, inscribing in the social imaginary the idea, still current, that the "homosexual being " is an essence to which conforms a fixed identity. Considering that religions shape subjectivities, this work investigates how the Catholic religion, predominant in Brazil, contributes to building the self-image of gays and lesbians. Since Catholicism is patriarchal, we inquire into the kind of relationship between the gender inequality present in Catholicism and the formation of the social identity of the homosexuals. For that, we focused on the concepts of identity, gender and religion in their various interconnections, beginning from a foucaultian point of view, also approaching to the social constructionism. The data of the empiric field were collected from two focal groups: one group composed of men, and the other composed of women that declare themselves gays and lesbians respectively. By the conducted theoretical discussions and analysis of focal groups, we found out that Catholicism contributes significantly to the negative perception that gays and lesbians have of themselves by labeling homosexuality as morally illegitimate and by inculcating on the homosexual people, very early in their lives, the concepts of sin, shame and guilt that strongly influence them. We could also conclude that the marks of gender used by the Catholicism to condemn the homosexuality influences in different ways the building up of the gay and of the lesbian identities